1973
DOI: 10.1111/j.1348-0421.1973.tb00930.x
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Bacteriocinogenicity by Conjugation in Group D Streptococci

Abstract: Seventy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
20
0

Year Published

1976
1976
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 13 publications
5
20
0
Order By: Relevance
“…Such cell-to-cell contact may be mediated by a mechanism similar to that of Streptococcus faecalis (11,18,19,37); however, we have no further information indicating the precise mechanism.…”
Section: Resultsmentioning
confidence: 73%
“…Such cell-to-cell contact may be mediated by a mechanism similar to that of Streptococcus faecalis (11,18,19,37); however, we have no further information indicating the precise mechanism.…”
Section: Resultsmentioning
confidence: 73%
“…We began to obtain a number of these strains and found plasmids in most of them. One limiting aspect at first was the absence of an efficient approach to doing genetic studies; however, this changed dramatically with reports by Tomura et al 37 in Japan and Jacob and Hobbs 38 in the UK demonstrating conjugation. This was somewhat unexpected, due to a common belief in those days that conjugation was essentially a Gram-negative behavior (Streptomyces being the exception).…”
Section: New Territorymentioning
confidence: 88%
“…Brock et al [1] and Pleceas et al [3,4] reported the percentage of typability to be 50%, 62%, and 96.2% respectively. Tomura et al [7] have also reported a high (97.5%) percentage of typability. However the latter authors considered a zone of inhibition measuring 1 mm or more as positive.…”
mentioning
confidence: 93%
“…Enterocin typing of group D streptococci has been carried out by Brock et al [1], Pleceas et al [3,4], and Tomura et al [7] on strains isolated in their countries. However no such work has been done in India.…”
mentioning
confidence: 99%
See 1 more Smart Citation